Circulating heme oxygenase-1: Not a predictor of preeclampsia but highly expressed in pregnant women who subsequently develop severe preeclampsia - Sandrim, Valéria C. [UNESP]; Caldeira-Dias, Mayara [UNESP]; Bettiol, Heloisa; Barbieri, Marco Antonio; Cardoso, Viviane Cunha; Cavalli, Ricardo Carvalho (Wiley, 2018)
Preeclampsia is the major cause of maternal and fetal deaths worldwide. Circulating biomarker concentrations to predict preeclampsia must be determined. Therefore, the objective was to evaluate heme oxygenase-1 (HO-1) concentration in both plasma and urine samples from pregnant women before the development of preeclampsia and to identify a potential biomarker for preeclampsia development. We performed a case-control study nested in a prospective study cohort at University Hospital of the Ribeirao Preto Medical School, University of São Paulo (HCFMRP-USP), Ribeirao Preto, Brazil. Of 1400 pregnant women evaluated at 20-25 weeks of gestation, 460 delivered in hospitals outside our institution. Of 940 pregnant women who completed the protocol, 30 developed preeclampsia (cases, 14 cases of severe preeclampsia and 16 cases of mild preeclampsia). Healthy pregnant women (controls, n = 90) were randomly selected from the remaining 910 participants. HO-1 concentration was evaluated in plasma/urine samples by using a commercial enzyme-linked immunosorbent assay kit. We found similar HO-1 levels in the plasma and urine for case and control groups. In the subgrouped preeclampsia, lower plasma HO-1 levels were found in mild compared with severe preeclampsia. We conclude that plasma HO-1 levels were not altered at 20-25 weeks of gestation before the manifestation of preeclampsia symptoms. Pregnant women who subsequently develop severe preeclampsia show higher expression of HO-1. This may be indicative of important underlying pathophysiologic mechanisms that differentiate between mild and severe preeclampsia and may possibly be related to a higher prooxidative status even before the development of clinical symptoms.